Chinese Food Culture in Pakistan: Analysis of Chinese Food Culture within the Framework of the CPEC Project - Muhammad Asif; Abdoulaye M’Begniga; Majid Ali; Muhammad Usman (East Asian Journal of Multidisciplinary Research, 2022)
In philosophy, “culture” denotes something separate from nature. Sociology, like ethology, defines culture as "what a group of people shares and unifies," that is, what is learned, transmitted, formed, and produced. Culture is what sets individuals apart from one other and their origins. It includes all aspects of human life, including communication and contact. Food is a need of existence, not just a means of sustenance. It also influences how we assess and recognize people, as well as their culture. Cuisines and ingredients vary greatly across civilizations, resulting in a fusion of foods and cultures. Food doesn't matter how they eat or cook it as long as it represents them and their culture. Cuisine and culture are intertwined, as are religion and customs. The rising number of Chinese people visiting Pakistan to work on hundreds of CPEC projects and Pakistanis visiting China for various reasons has helped Chinese cuisine gain popularity in Pakistan. Food is one of the most exciting ways to learn about culture. Active or experiential learning improves comprehension and retention. This article addresses the relationship between culture and food, claiming that teaching food as culture may assist build cultural awareness and intelligence. This theoretical investigation used primary and secondary data. The primary sources were books, official Chinese and Pakistani databases, and bilateral agreements, while secondary sources included research papers, newspapers, journals, and internet databases.